Environmental analysis of rainwater harvesting infrastructures in diffuse and compact urban models of Mediterranean climate. - Angrill, Sara (The International Journal of Life Cycle Assessment)
Purpose. At present, many urban areas in Mediterranean climates are coping with water scarcity, facing a growing water demand and a limited conventional water supply. Urban design and planning has so far largely neglected the benefits of rainwater harvesting (RWH) in the context of a sustainable management of this resource. Therefore, the purpose of this study was to identify the most environmentally friendly strategy for rainwater utilization in Mediterranean urban environments of different densities. Materials and methods The RWH systems modeled integrate the necessary infrastructures for harvesting and using rainwater in newly constructed residential areas. Eight scenarios were defined in terms of diffuse (D) and compact (C) urban models and the tank locations ((1) underground tank, (2) below-roof tank, (3) distributed over roof tank, and (4) block tank). The structural and hydraulic sizing of the catchment, storage and distribution subsystems was taken into account using an average Mediterranean rainfall, the area of the harvesting surfaces, and a constant water demand for laundry. The quantification of environmental impacts was performed through a life cycle assessment, using CML 2001 Baseline method. The necessary materials and processes were considered in each scenario according to the lifecycle stages (i.e. materials, construction, transportation, use and deconstruction) and subsystems. Results and discussion. The environmental characterization indicated that the best scenario in both urban models is the distributed over roof tank (D3, C3), which provided a reduction in impacts compared to the worst scenario of up to 73 percent in diffuse models and even higher in compact ones, 92 percent in the most dramatic case. The lower impacts are related to the better distribution of tank weight on the building, reducing the reinforcement requirements, and enabling energy savings. The storage subsystem and the materials stage contributed most significantly to the impacts in both urban models. In the compact density model, the underground tank scenario (C1) presented the largest impacts in most categories due to its higher energy consumption. Additionally, more favorable environmental results were observed in compact densities than in diffuse ones for the Global Warming Potential category along with higher water efficiencies. Conclusions. The implementation of one particular RWH scenario over another is not irrelevant in drought stress environments. Selecting the most favorable scenario in the development of newly constructed residential areas provides significant savings in CO2 emissions in comparison with retrofit strategies. Therefore, urban planning should consider the design of RWH infrastructures using environmental criteria in addition to economic, social and technological factors, adjusting the design to the potential uses for which the rainwater is intended. Recommendations and perspectives Additional research is needed to quantify the energy savings associated with the insulation caused by using the tank distributed over the roof. The integration of the economic and social aspects of these infrastructures in the analysis, from a life cycle approach, is necessary for targeting the planning and design of more sustainable cities in an integrated way.